Potential of Mangiferin (Mangifera Indica Linn) in Accelerating Bone Remodeling Process to Prevent Relapse after Orthodontic Treatment - Yenita Alamsyah; Azmil Hadi; Edrizal Edrizal (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Relapse is a problem that still often occurs and results in a decrease in the success of orthodontic treatment. Bone remodeling is beneficial in orthodontic treatment especially to prevent relapse of treatment results. Osteoblasts and osteoclasts have a very important role during the bone remodeling process. Mangiferin (Mangifera indica Linn) has good biocompatible properties on bone. Mangiferin as an immunomodulator, inhibits osteoclast formation and bone resorption by inhibiting the RANKL pathway and has anti-resorptive properties. Aim: The purpose of this study was to prove that mangiferin (Mangifera indica Linn) has the potential to help the bone remodeling process to prevent relapse after orthodontic treatment. Methods: Standardized mangiferin was made to produce hydrogel with a concentration of 6.25% and 12.5%. The research samples were 36 male Wistar rats (Rattus novergicus) aged 3-4 months with the positive control (nickel-titanium closed coil installed without mangiferin application), and treatment group (nickel-titanium closed coil installed with mangiferin application with concentrations of 6.25% and 12.5%). Installation of ni-ti closed coil spring on maxillary incisors and molars for 10 days. A constant force of 10 gr/mm2 was generated using a ni-ti closed coil spring to move the maxillary first molars mesially. Spring was attached to the first molar and maxillary right incisor using a stainless wire ligature and then released. After removal, mangiferin hydrogel was applied twice a day for 14 days and decapitated on days 1, 3, 5, 7, and 14. Histological examination with hematoxylin and eosin staining to see osteoblasts and osteoclasts. Results: The increase in reactive osteoblasts was higher than osteoclasts indicating post- orthodontic bone remodeling. Both osteoblast and osteoclast profiles were significantly different (p<0.05). Conclusion: Mangiferin (Mangifera indica Linn) has the ability to induce osteoblasts in bone formation and inhibit osteoclast differentiation to accelerate the bone remodeling process to prevent relapse after orthodontic treatment